2020
DOI: 10.3389/fimmu.2020.549889
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Synergize With P2 Receptors to Regulate Human T Cell Function

Abstract: Intracellular ATP is the universal energy carrier that fuels many cellular processes. However, immune cells can also release a portion of their ATP into the extracellular space. There, ATP activates purinergic receptors that mediate autocrine and paracrine signaling events needed for the initiation, modulation, and termination of cell functions. Mitochondria contribute to these processes by producing ATP that is released. Here, we summarize the synergistic interplay between mitochondria and purinergic signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 113 publications
1
14
0
Order By: Relevance
“…For example, the addition of apyrase, an ATP scavenger, can reduce Hst 5-mediated killing, suggesting a direct connection between released ATP and C. albicans cell death [ 62 ]. Moreover, released ATP modulates functions of immune cells through its activation of purinergic receptors [ 63 ]. Although the underlying mechanisms are not fully understood, treatment with purinergic antagonists prevents Hst 5-mediated C. albicans killing [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the addition of apyrase, an ATP scavenger, can reduce Hst 5-mediated killing, suggesting a direct connection between released ATP and C. albicans cell death [ 62 ]. Moreover, released ATP modulates functions of immune cells through its activation of purinergic receptors [ 63 ]. Although the underlying mechanisms are not fully understood, treatment with purinergic antagonists prevents Hst 5-mediated C. albicans killing [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on mitochondria in ME/CFS patients have shown altered membrane potential, condensed cristae and reduced ATP production ( 59 , 62 , 63 ). Mitochondria are responsible for controlling cell death, stimulating inflammatory pathways, and producing ATP involved in purinergic signaling ( 35 , 64 ). Furthermore, neuroinflammation activates microglia that release reactive oxygen species and reactive nitrogen species that have a deleterious effect on mitochondria ( 65 ).…”
Section: Evidence Of An Ongoing Systemic Peripheral Immune/inflammato...mentioning
confidence: 99%
“…A cycling of molecular “danger signaling” signals between the systemic innate immune system and brain's innate immune system may then be set up and persist. This might occur for example, from damaged mitochondria acting as a signaling organelle, for example with leakage of ATP and subsequent purinergic signaling to the microglia ( 35 ). A dysfunctional physiology, with a dysregulated cellular molecular biology also becoming a critical facet, results in a disruption of the normal carefully balanced homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as the energy centers of cell activities, mitochondria are also critical for maintaining T-cell function (Vardhana et al, 2020;Yu et al, 2020). Mitochondria interact with the P2X1, P2X4, and P2Y11 receptors to regulate T-cell metabolism, cell migration, and antigen recognition (Ledderose and Junger, 2020). T-cell mitochondrial dysfunction can lead to premature aging (Lenaers et al, 2020), and distorted mitochondrial metabolism has a role in driving In previous studies on TCF1, researchers have typically focused on CD8 + T-cells (Chen et al, 2021;Rutishauser et al, 2021;Zhao et al, 2021), with scant literature on the role of TCF1 in CD4 + T-cells.…”
Section: Discussionmentioning
confidence: 99%